2019
DOI: 10.2147/cpaa.s207258
|View full text |Cite
|
Sign up to set email alerts
|

<p>Vitamin B12 deficiency presenting as pseudo-thrombotic microangiopathy: a case report and literature review</p>

Abstract: Pseudo-thrombotic microangiopathy (pseudo-TMA) is a recognized, yet uncommon, clinical presentation of vitamin B12 deficiency. Patients with pseudo-TMA present with microangiopathic hemolytic anemia (MAHA), thrombocytopenia and schistocytes. They are often misdiagnosed as thrombotic thrombocytopenia purpura (TTP) and receive unnecessary therapy. Here, we report a case of a 60-year-old male who presented with thrombocytopenia and normocytic normochromic anemia. Anemia work-up was remarkable for severe B12 defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 19 publications
(21 reference statements)
0
27
0
Order By: Relevance
“…It is speculated that the etiology of dysmorphic red blood cells in severe vitamin B12 deficiency stems from both intramedullary and extramedullary dysfunction. From an extramedullary perspective, research has shown that hyperhomocysteinemia, which occurs in vitamin B12 deficiency, may increase the risk of hemolysis in addition to causing endothelial damage, which further leads to intravascular hemolysis and RBC fragmentation [ 6 ]. Of note, hyperhomocysteinemia can also be caused by hypothyroidism, obesity, diabetes, hyperlipidemia, medications, and more rarely possessing a methylenetetrahydrofolate reductase gene variant [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that the etiology of dysmorphic red blood cells in severe vitamin B12 deficiency stems from both intramedullary and extramedullary dysfunction. From an extramedullary perspective, research has shown that hyperhomocysteinemia, which occurs in vitamin B12 deficiency, may increase the risk of hemolysis in addition to causing endothelial damage, which further leads to intravascular hemolysis and RBC fragmentation [ 6 ]. Of note, hyperhomocysteinemia can also be caused by hypothyroidism, obesity, diabetes, hyperlipidemia, medications, and more rarely possessing a methylenetetrahydrofolate reductase gene variant [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although TTP can be deadly without any proper therapy plan, starting plasmapheresis treatment for TTP and vitamin B12 replacement for cobalamin deficiency might be a plausible choice for pseudo-TMA-suspected cases [ 14 ]. One of the features that assist in primary diagnosis is that pseudo-TMA does not respond to FFP, which was the case in our report [ 1 ].…”
Section: Discussionmentioning
confidence: 93%
“…Every vitamin is assigned a specific and unique role in the human body, for instance, “vitamin B12" is one of the most vital vitamins with its unique structure and composition of the mineral cobalt and thus the origin of the name cobalamin. It possesses various roles on different levels, including DNA and red blood cell (RBC) synthesis, in addition to several neurologic functions [ 1 ]. The cut-off was defined by the World Health Organization, where cobalamin deficiency was presented as less than 150 pmol/L [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be reflected by the presence of schistocytes (Figure 1) and bizarre anisopoikilocytosis on the peripheral blood smear (Figure 2). These abnormal blood findings can affect the mean corpuscular volume; however, it has been found to be normal in less than 50% of the patients [9]. Moreover, D-dimer levels can also be elevated in some patients due to activation of the coagulation cascade and co-relate well with the degree of schistocytosis [2].…”
Section: Discussionmentioning
confidence: 99%